Influence of the spatial distribution of border traps in the capacitance frequency dispersion of Al2O3/InGaAs - Palumbo, Félix Roberto Mario; Aguirre, Fernando Leonel; Pazos, Sebastián Matías; Krylov, Igor; Winter, Roy; Eizenberg, Moshe (Pergamon-Elsevier Science Ltd, 2018)
Fil: Palumbo, Félix Roberto Mario. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Tecnológica Nacional; Argentina